2013
DOI: 10.1002/cam4.154
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of salvage stereotactic radiotherapy for recurrent glioma: impact of tumor morphology and method of target delineation on local control

Abstract: In this study, we assessed the efficacy of salvage stereotactic radiotherapy (SRT) for recurrent glioma. From August 2008 to December 2012, 30 patients with recurrent glioma underwent salvage SRT. The initial histological diagnoses were World Health Organization (WHO) grades II, III, and IV in 6, 9, and 15 patients, respectively. Morphologically, the type of recurrence was classified as diffuse or other. Two methods of clinical target delineation were used: A, a contrast-enhancing tumor; or B, a contrast-enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…A further millimetric margin is usually added to the CTV to create a planning target volume (PTV). As reported by some authors 11,15,51 , we also included the area of peritumoral edema, defined on the Flair sequences with a 2-mm margin expansion, in the PTV Flair, whereas the PTV-boost was defined as the visible tumor on enhanced T1-MRI with a 1-mm margin expansion.…”
Section: Discussionmentioning
confidence: 99%
“…A further millimetric margin is usually added to the CTV to create a planning target volume (PTV). As reported by some authors 11,15,51 , we also included the area of peritumoral edema, defined on the Flair sequences with a 2-mm margin expansion, in the PTV Flair, whereas the PTV-boost was defined as the visible tumor on enhanced T1-MRI with a 1-mm margin expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiotherapy could be an option for the treatment of unresectable gliomas, even as an initial treatment (5)(6)(7)19). However, cases 1 and 2 received obvious overdose of radiation by an additional stereotactic radiotherapy and presented with repeated hemorrhages, medically uncontrollable symptomatic epilepsy, and cerebral edema.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy is a less invasive treatment for brain and neck diseases, such as head and neck cancers and arteriovenous malformations (1)(2)(3)(4). Although some studies reported the efficacy of stereotactic radiation therapy for either newly diagnosed glioma or recurrent glioma, especially for lesions that are unamenable to resection, such as lesions of eloquent areas of the brain, strong recommendation of stereotactic radiation therapy for glioma has not yet been established (5)(6)(7). Necrosis, cavernous malformation, and radiation-induced tumor formation are major side effects observed in the latter stages of radiation therapy; these side effects sometimes distress the patients (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, Glass et al 20 tested this combined approach of stereotactic radiotherapy and chemotherapy with cisplatin. Since then, several studies that combined HFSRT with various drugs (paclitaxel, TMZ, topotecan, gefitinib, sunitinib, fotemustine, panobinostat, or bevacizumab) 20 , 23 , 27 , 28 , 30 , 33 , 35 - 38 , 40 , 41 , 43 - 46 have been conducted. According to these studies, combined modality management appears to be feasible and well tolerated, and the results are encouraging especially with bevacizumab.…”
Section: Discussionmentioning
confidence: 99%